Educational Transformation in Islamic Higher Education in Response to Global Challenges - Muhammad Usaid; Donatella Camedda; Ita Tryas Nur Rochbani (CV. Zabags Qu Publish, 2026)
This study aims to a civilization that is already familiar with information and communication technology (ICT) is known as